EFFECTIVENESS OF SOIL HERBICIDES APPLICATION IN GRAIN CORN AREAS - Milenko, О. H.; Horiachun, K. V.; Zviaholsky, V. V.; Kozynko, R. А.; Karpinska, S. О. (Scientific Progress & Innovations, 2020)
The primary problem of modern agricultural production is the study and implementation of the effective measures of weed control in crop areas. The purpose of our research was to establish the effectiveness of soil herbicides application in corn areas, substantiation of recommendations for improving the elements of cultivation technology of corn in the Forest-Steppe of Ukraine. Field experiment in five variants: control (without herbicides and manual weeding), that is, with natural weed infestation; four experimental variants using Avanhard, 2.0 l/ha; Blokpost, 1.4 l/ha; Kratos, 2.0 l/ha and Kratos, 2.5 l/ha herbicides was set up dur-ing the period of 2017–2019. Spraying the soil with herbicides was carried out immediately after sowing corn. Species and number of weeds were determined on the plots with natural weed infestation, where no weed control measures were conducted. The application of Avanhard preparation at the rate of 2 l/ha led to the reduction of gramineous weeds by 96.3 %, and dicotyledonous weeds only by 28.6 %. The application of Blokpost preparation at the rate of 1.4 l/ha reduced gramineous weeds by 81.5 % and dicotyledonous weeds by 60.7 %. The application of Kratos at the rate of 2.0 l/ha was effective against gramineous weeds by 85.2 % and against dicotyledonous weeds by 78.6 %. The application of Kratos with the increased rate of using up to 2.5 l/ha increased the mortality of gramineous weeds by 92.6 %, and dicotyledonous weeds by 82.1 %. As a result of calculating corn plants, it has been found that in the experimental variants with herb-icide spraying, plant stand did not vary significantly. The conditions of natural competition between corn and weeds had the worst effect on crop density. The weather conditions of 2018 had the best influence on corn grain yield, while 2019 was the most unfavorable year. The maximum yield of 9.4 t/ha was obtained in the experiment variant, in which Kratos preparation was used at the rate of 2.5 l/ha. According to the eco-nomic evaluation of the effectiveness of the developed corn for grain cultivation technology elements, we recommend to apply Kratos preparation (2.5 l/ha) under mixed type of field weed infestation.